Preparation method of multi-component synergistically modified solid-state lithium battery

CN122968451APending Publication Date: 2026-10-23CHENGDU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611215490.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0003]然而,随着电池能量密度与循环寿命要求不断提升,热失控等安全风险问题备受关注

Benefits of technology

[0019](1)与聚偏氟乙烯(PVDF)基固态电解质相比,引入 PVDF-HFP 基固态电解质中的六氟丙烯(HFP)结构单元可有效降低聚合物体系的结晶度,提升离子传输性能。因此,PVDF-HFP呈现双相结晶特征。一方面,向 PVDF 中引入无定形 HFP 链段能够提高低结晶区域的氟含量,增强材料疏水性及其在多种溶剂中的溶解性,进一步提升锂离子电导率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968451A_ABST
    Figure CN122968451A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of lithium battery materials, and particularly relates to a preparation method of a multi-component synergistically modified solid-state lithium battery, which mainly comprises preparation of a composite solid-state electrolyte film and assembly of the battery. The present application uses polyvinylidene fluoride-hexafluoropropylene, lithium salt and N-methyl pyrrolidone as raw materials, adds plasticizers, interfacial modifiers and nano-hydroxyapatite to prepare a composite solid-state electrolyte film in a multi-component synergistic manner, thereby improving the mechanical strength of the solid-state electrolyte, providing more transmission channels for migration of lithium ions, improving the electric capacity of the electrolyte and enhancing the cycle stability of the lithium metal battery. In the present application, PVDF-HFP forms hydrogen bonds with nano-hydroxyapatite, thereby improving the electrochemical performance, reducing the crystallinity of PVDF-HFP and avoiding short circuit and explosion caused by dendrite puncture of the separator. The present application solves the safety hazards caused by traditional liquid electrolytes, such as leakage, combustion and explosion, and has the advantages of simple preparation method, low cost and suitability for industrial large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium battery material technology, specifically relating to a method for preparing a multi-component synergistically modified solid-state lithium battery. Background Technology

[0002] The development of electric vehicles, energy storage, and consumer electronics industries has driven the demand for high-safety, high-energy-density batteries. Lithium metal batteries, with their ultra-high theoretical specific capacity and extremely low redox potential, have become a research hotspot for next-generation energy storage systems. However, liquid electrolyte systems suffer from severe interfacial side reactions and low coulombic efficiency, and low-temperature environments further deteriorate lithium-ion transport and lithium deposition behavior. Solid-state electrolytes, with their excellent mechanical and electrochemical stability, can effectively suppress lithium dendrites and improve the lithium anode interface, making them the most promising pathway to achieving long-cycle, high-safety lithium metal batteries.

[0003] However, with the increasing demands for battery energy density and cycle life, safety risks such as thermal runaway have become a major concern. Conventional polymer solid-state electrolytes (SPEs) have insufficient room-temperature ionic conductivity (<10⁻⁻⁴). 6 The poor mechanical properties, coupled with poor solid-solid interface contact and high interfacial impedance, limit the development of solid-state lithium metal batteries. Existing modification methods mostly rely on single fillers or additives for optimization, making it difficult to balance ionic conductivity, mechanical properties, and interfacial stability, and simultaneously optimize these properties. For example, Jie Wen et al. (“Hydroxyapatite Nanowire-Reinforced Poly(ethylene oxide)-Based Polymer Solid Electrolyte for Application in High-Temperature Lithium Batteries”) introduced HAP as a filler, but the resulting solid electrolyte had an ionic conductivity of only 1.05 × 10⁻¹⁰. −5 With S / cm, it is difficult to achieve simultaneous optimization of various performance aspects.

[0004] Therefore, developing a lithium battery that can synergistically balance ionic conductivity, mechanical properties, and interface stability has significant practical implications and promising development prospects. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and to provide a method for preparing a multi-component synergistic modified solid-state lithium battery.

[0006] The objective of this invention is achieved through the following technical solution: a method for preparing a multi-component synergistically modified solid-state lithium battery, comprising the following steps:

[0007] S1. Preparation of composite solid electrolyte membrane:

[0008] Polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and lithium salt are mixed and then nitrogen-methylpyrrolidone (NMP) is added. The mixture is stirred at 30-70°C for 3-8 hours until the polymer is fully dissolved. Then, a plasticizer and an interface modifier with a volume ratio of 4-10:1-6 are added, and the mixture is stirred at 40-80°C for 3-8 hours until the solution is transparent. Finally, a nano-hydroxyapatite (HAP) solution is added and mixed evenly. The resulting slurry is coated, dried, and cut into sheets. This invention prepares a multi-component synergistic modified composite solid electrolyte membrane (PLSFH). Preferably, the coating thickness is 100-1000 μm.

[0009] S2. Assemble the battery: Assemble the composite solid electrolyte membrane prepared in step S1 into a lithium metal battery to obtain a polyvinylidene fluoride-hexafluoropropylene-based multi-component synergistic composite modified solid lithium battery.

[0010] As a preferred technical solution, the plasticizer is at least one selected from adiponitrile, malononitrile, succinic anhydride, glutaronitrile, azelonium, heptacyanide, caprylic anhydride, or sebacate.

[0011] As a preferred technical solution, the lithium salt is any one of LiPF6, LiTFSI, LiFSI, LiBOB, LiDFOB, LiBF4, LiClO4 or LiAsF6.

[0012] As a preferred technical solution, the interface modifier is at least one of fluoroethylene carbonate, ethylene carbonate, and propylene carbonate.

[0013] As a preferred technical solution, the mass ratio of polyvinylidene fluoride-hexafluoropropylene to lithium salt is 2:1 to 7:3; the solid-liquid ratio (g:mL) of solvent and mixed powder is 1:15 to 5:23; the volume ratio of plasticizer and interface modifier is 3:1 to 9:5; and the amount of nano-hydroxyapatite added is 0.05% to 3.0% of the total weight of solute.

[0014] As a preferred technical solution, the positive electrode sheet of the lithium-ion battery in step S2 is prepared by the following method: polyvinylidene fluoride and plasticizer are added to nitrogen-methylpyrrolidone and stirred overnight to obtain a transparent solution. Lithium iron phosphate and acetylene black are ground and mixed evenly in a grinding mortar. The transparent liquid is then added to the grinding mortar and ground until the slurry becomes black and viscous. The ground slurry is coated onto aluminum foil and placed in a drying oven at 40-80°C for 10-48 hours. The foil is then cut into round pieces using a cutting machine.

[0015] As a preferred technical solution, the plasticizer is at least one selected from malononitrile, succinic anionitrile, glutaronitrile, adiponitrile, heptacyanide, octanoic anionitrile, azelaic anionitrile, or sebacate; the weight ratio of lithium iron phosphate, polyvinylidene fluoride, acetylene black, and plasticizer is 6-10:0.1-2:0.1-2:0.1-2; the volume ratio of N-methylpyrrolidone to the mass ratio of lithium iron phosphate is 1-10 mL:1-3 g.

[0016] As a preferred technical solution, the lithium-ion battery assembly in step S2 is performed in the following order: positive electrode shell, positive electrode sheet, solid electrolyte membrane, negative electrode, stainless steel sheet, spring sheet, and negative electrode shell. The assembled battery is then placed on a battery sealing machine and pressurized to 450–650 kg·cm². -2 .

[0017] In this invention, the negative electrode is a lithium metal sheet with a diameter of 15.6 mm and a thickness of 0.6 mm.

[0018] In this invention: 1. Using PVDF-HFP (polyvinylidene fluoride-hexafluoropropylene) as the solid electrolyte substrate has the following advantages:

[0019] (1) Compared with polyvinylidene fluoride (PVDF)-based solid electrolytes, the introduction of hexafluoropropylene (HFP) structural units into PVDF-HFP-based solid electrolytes can effectively reduce the crystallinity of the polymer system and improve ion transport performance. Therefore, PVDF-HFP exhibits biphase crystallization characteristics. On the one hand, the introduction of amorphous HFP segments into PVDF can increase the fluorine content in the low crystallinity region, enhance the hydrophobicity of the material and its solubility in various solvents, and further improve the lithium-ion conductivity.

[0020] (2) Reduced crystallinity: Compared to PVDF, PVDF-HFP has a lower glass transition temperature, which can reduce the crystallinity of the polymer matrix. This structure can generate strong polarization during lithium salt dissociation, thereby improving ionic conductivity.

[0021] (3) High mechanical strength: The crystalline phase (-VDF) in PVDF-HFP can play a role in mechanical support, which makes PVDF-HFP have good mechanical properties and excellent heat resistance.

[0022] (4) Improved ionic conductivity: Ion transport within the PVDF-HFP based solid electrolyte relies on the interaction between polar fluorinated groups in the polymer matrix and lithium ions. These polar groups construct effective dissolution and migration channels for lithium ions, thereby achieving ion conduction.

[0023] (5) Low cost: PVDF has excellent flexibility, is easy to process and mold, and can be used for batteries of various shapes. The processing technology is simple and easy to achieve large-scale production.

[0024] (6) Good conductivity and high energy density: PVDF has a high dielectric constant and strong polar groups (-CF-) which promote the dissolution of lithium salts, thereby forming a high concentration of charge carriers. Therefore, it has a strong affinity for electrolytes. The large lithium ion transference number helps to reduce polarization caused by concentration difference during charging and discharging, thus enabling the battery to have a higher energy density.

[0025] 2. Using nano-hydroxyapatite as a filler has the following advantages:

[0026] (1) Constructing a continuous ion transport pathway to reduce polymer crystallinity: Inorganic nano-HAP is uniformly dispersed in the PVDF-HFP matrix, which acts as a physical barrier, interfering with the orderly stacking of polymer chain segments, further reducing polymer crystallinity and expanding the amorphous region. The amorphous phase is the main lithium-ion transport channel, thus accelerating Li⁺ migration.

[0027] (2) Improve the mechanical properties of the electrolyte and enhance mechanical stability: Nano HAP is incorporated into the polymer matrix as a rigid inorganic filler, which improves the tensile strength and modulus of the composite film. The higher mechanical strength can physically block lithium dendrite puncture, reduce the risk of battery short circuit, and improve the safety performance of solid-state batteries.

[0028] (3) Optimize interface wettability and reduce solid-solid interface voids: Polar hydroxyl groups give HAP good affinity, improve the interfacial contact between PVDF-HFP electrolyte and lithium metal anode, reduce interfacial pores and contact impedance, and improve lithium ion cross-interface transport dynamics.

[0029] (4) Expanding the electrochemical stability window: The stable filler and passivated SEI work together to enhance the antioxidant capacity of the electrolyte system and expand the electrochemical window.

[0030] (5) Improved thermal stability: Inorganic fillers restrict the high-temperature movement of PVDF-HFP molecular chains, inhibit polymer melting and flow, broaden the stable operating temperature range of electrolyte, and improve battery thermal safety.

[0031] (6) Constructing a stable interface: Nano-hydroxyapatite can effectively bind TFSI⁻ anions and reconstruct the Li⁺ solvated sheath layer, reducing the occurrence of side reactions.

[0032] 3. Environmentally friendly: The materials used in solid-state batteries do not cause pollution to the environment in most cases, which reflects their environmental friendliness.

[0033] 4. Simple process and low cost: The processing technology of polymer solid electrolytes is simple and easy to achieve large-scale production.

[0034] 5. Synergistic effects of multiple components break the contradiction between mechanical strength and ionic conductivity, effectively suppressing lithium dendrite growth and improving the long-cycle performance of solid-state batteries.

[0035] The present invention has the following advantages:

[0036] (1) The synergistic effect of multiple components breaks the balance between ionic conductivity and mechanical strength, effectively suppresses lithium dendrite growth, and significantly improves the interface stability and long cycle life of solid lithium batteries.

[0037] (2) Using nano-hydroxyapatite as a filler can improve the mechanical strength of the electrolyte membrane, reduce crystallinity, increase lithium ion migration channels, improve ionic conductivity, improve the interfacial contact between electrolyte and lithium metal, and reduce interfacial impedance.

[0038] (3) By modifying PLSFH with multiple components, a stable ion transport channel is constructed, the lithium ion transference number is increased, a stable SEI interface is constructed, and its electrochemical performance and long cycle life are improved.

[0039] (4) PLSFH has a wide electrochemical stability window, which enables the battery to operate stably over a wider voltage range to accommodate different types of electrode materials and broaden the electrochemical stability window. Attached Figure Description

[0040] Figure 1 The tensile test results are for the electrolyte membrane PLSFH prepared in Example 1 of this invention;

[0041] Figure 2 The discharge performance of LFP||Li solid coin cells assembled using the solid electrolyte PLSFH prepared in Example 1 of this invention at rates of 0.1C, 0.2C, 0.3C, 0.5C, and 1C is shown. Figure 2 In the figures: (a) represents the test results at a 0.1C expansion ratio; (b) represents the test results at a 0.2C expansion ratio; (c) represents the test results at a 0.3C expansion ratio; (d) represents the test results at a 0.5C expansion ratio; (e) represents the test results at a 1C expansion ratio.

[0042] Figure 3 The capacity recovery of LFP||Li solid coin cells assembled using the solid electrolyte PLSFH prepared in Example 1 of this invention under different discharge rates is shown.

[0043] Figure 4The capacity retention of LFP||Li solid coin cells assembled using the solid electrolyte PLSFH prepared in Example 1 of this invention after 300 cycles at 0.5C rate is shown.

[0044] Figure 5 To assemble a Li||Li solid-state coin cell lithium battery using the solid electrolyte PLSFH prepared in Example 1 of this invention at room temperature with a loading rate of 0.2 mA cm⁻¹ -2 The stability of constant current charge and discharge over long cycles at the current density. Detailed Implementation

[0045] To explain the technical content, objectives, and effects of the present invention in detail, the following specific embodiments are provided to further illustrate the content of the present invention. However, the content of the present invention is far more than the following examples.

[0046] In the following embodiments, unless otherwise specified, the "solid-liquid ratio" refers to the ratio of solid mass to liquid volume (g:mL). For example, "3:18" means 3g of solid to 18mL of liquid.

[0047] Example 1: A method for preparing a multi-component synergistically modified solid-state lithium battery, comprising the following steps:

[0048] (1) Preparation of positive electrode sheet: Lithium iron phosphate (LFP) and acetylene black are ground in an agate grinding mortar to mix the two powders evenly. Polyvinylidene fluoride and plasticizer (malononitrile) are added to nitrogen-methylpyrrolidone (NMP) and stirred overnight to obtain a transparent solution. The transparent liquid is added to the grinding mortar and mixed with LFP and acetylene black, and grinding is continued until the slurry becomes a black and viscous slurry. The slurry is coated onto aluminum foil, placed in a drying oven and dried at 50°C for 24 hours, and cut into round sheets with a diameter of 12 mm using a cutting machine. The weight ratio of lithium iron phosphate, polyvinylidene fluoride, acetylene black and plasticizer is 6:0.1:0.1:0.1, and the volume ratio of nitrogen-methylpyrrolidone to lithium iron phosphate is 1 mL:1 g.

[0049] (2) Preparation of composite solid electrolyte membrane: 0.6g of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and lithium salt (LiTFSI) were mixed and then nitrogen-methylpyrrolidone (NMP) was added. The mixture was stirred at 60°C for 8 hours until the polymer was fully dissolved. Then, plasticizer (butonitrile) and interface modifier (fluoroethylene carbonate) were added. The mixture was stirred at 60°C for 4 hours until the solution was transparent. Then, nano-hydroxyapatite solution was added and mixed evenly. The resulting slurry was coated, dried and cut into sheets. The multi-component synergistic modified composite solid electrolyte membrane (PLSFH) was prepared by this invention. Among them, the mass ratio of polyvinylidene fluoride-hexafluoropropylene and lithium salt was 4:1, the solid-liquid ratio of reagent and mixed powder was 3:18; the volume ratio of 210 μL plasticizer (butonitrile) and interface modifier (fluoroethylene carbonate) was 7:3, and the amount of nano-hydroxyapatite added was 1% of the total weight of solute;

[0050] (3) Selection of negative electrode: The negative electrode is a lithium metal sheet with a diameter of 15.6 mm and a thickness of 0.6 mm.

[0051] (4) Battery assembly: The lithium battery is assembled in the following order: positive electrode shell, positive electrode plate, solid electrolyte membrane, negative electrode, stainless steel sheet, spring sheet, and negative electrode shell. The assembled battery is placed on a battery sealing machine and pressurized to 500 kg·cm. -2 .

[0052] Tensile test

[0053] Tensile tests were performed using the electrolyte prepared in Example 1. Figure 1 As shown, the modified electrolyte membrane exhibits significantly improved elongation at break and tensile strength, with an elongation at break reaching 98.7% and a tensile strength reaching 13.11 MPa.

[0054] Electrochemical performance testing:

[0055] The electrolyte PLSFH prepared using Example 1 has an ionic conductivity of 2.15 × 10⁻⁶ at room temperature. -4 S / cm.

[0056] The electrolyte PLSFH prepared in Example 1 was used to assemble coin cells using methods known in the art. Cyclic performance and capacity recovery performance at different rates were tested at 0.1C, 0.2C, 0.3C, 0.5C, and 1C, respectively, with a capacitance of 0.2 mA cm⁻¹. -2 Constant current charge-discharge tests were performed using the current density, and the results are as follows: Figure 2 , Figure 3 , Figure 4 , Figure 5 As shown.

[0057] from Figure 2It can be seen that: at a 0.1 C rate, the initial discharge capacity can reach 167.1 mAh / g, and the coulombic efficiency is 99.53%; from Figure 2 b shows that at a 0.2 C rate, the initial discharge specific capacity can reach 150.3 mAh / g, and the coulombic efficiency is 98.18%; from Figure 2 c shows that at a 0.3 C rate, the initial discharge specific capacity can reach 148.4 mAh / g, and the coulombic efficiency is 99.02%; from Figure 2 As can be seen from d, the initial discharge specific capacity at a 0.5 C rate can reach 136.1 mAh / g, with a coulombic efficiency of 98.14%. From Figure 2 As can be seen from d: at a 0.5 C rate, the initial discharge specific capacity can reach 136.1 mAh / g, and the coulombic efficiency is 98.14%; from Figure 2 As can be seen from the above, the initial discharge specific capacity at a 1 C rate can reach 116.1 mAh / g, and the coulombic efficiency is 98.91%.

[0058] from Figure 3 It can be seen that the coulombic efficiency is maintained at different rates, and after cycling at 1C and then returning to 0.1C, the discharge specific capacity immediately increases and is on par with the discharge specific capacity at the first 0.1C.

[0059] from Figure 4 It can be seen that the capacity retention rate reaches 95% after 300 cycles at a 0.5C rate.

[0060] from Figure 5 It can be seen that the assembled solid-state lithium battery, at room temperature, has a current of 0.2 mA cm⁻¹ -2 The constant current charge-discharge cycle can be stably maintained for more than 850 hours, demonstrating good stability.

[0061] Example 2

[0062] This embodiment is based on Example 1, except that the mass ratio of polyvinylidene fluoride-hexafluoropropylene and lithium salt in preparation step (2) is adjusted to 2:1. All other materials, process parameters and processes are the same as in Example 1.

[0063] After fabricating the coin-type lithium battery, electrochemical tests were conducted. The initial discharge specific capacity at 0.1C rate was 158.6 mAh / g, and the coulombic efficiency was 98.72%.

[0064] Example 3

[0065] This embodiment is based on Example 1, except that the mass ratio of polyvinylidene fluoride-hexafluoropropylene and lithium salt in preparation step (2) is adjusted to 5:2. All other materials, process parameters and processes are the same as in Example 1.

[0066] After fabricating the coin-type lithium battery, electrochemical tests were conducted. The initial discharge specific capacity at 0.1C rate was 160.1 mAh / g, and the coulombic efficiency was 99.19%.

[0067] Example 4

[0068] This embodiment is based on Example 1, except that the mass ratio of polyvinylidene fluoride-hexafluoropropylene and lithium salt in preparation step (2) is adjusted to 7:3. All other materials, process parameters and processes are the same as in Example 1.

[0069] After fabricating the coin-type lithium battery, electrochemical tests were conducted. The initial discharge specific capacity at 0.1C rate was 158.3 mAh / g, and the coulombic efficiency was 99.73%.

[0070] Example 5

[0071] This embodiment is based on Example 1, except that the solid-liquid ratio of the reagent and the mixed powder in step (2) is 1:15. All other materials, process parameters and processes are the same as in Example 1.

[0072] After fabricating the coin-type lithium battery, electrochemical tests were conducted. The initial discharge specific capacity at 0.1C rate was 156.6 mAh / g, and the coulombic efficiency was 98.29%.

[0073] Example 6

[0074] This embodiment is based on Example 1, except that the solid-liquid ratio of the reagent and the mixed powder in step (2) is 5:23. All other materials, process parameters and processes are the same as in Example 1.

[0075] The prepared electrolyte has an ionic conductivity of 1.02 × 10⁻⁶. -4 S / cm, after preparing coin-type lithium batteries, electrochemical tests were performed. The initial discharge specific capacity at 0.1C rate was 159.5 mAh / g, and the coulombic efficiency was 99.06%.

[0076] Example 7

[0077] This embodiment is based on Example 1, except that the ratio of plasticizer to interface modifier in step (2) is 3:1. All other materials, process parameters and processes are the same as in Example 1.

[0078] The prepared electrolyte membrane was subjected to tensile testing, and its tensile strength was 6.55 MPa and its elongation at break was 78.29%.

[0079] Example 8

[0080] This embodiment is based on Example 1, except that the product ratio of plasticizer and interface modifier in preparation step (2) is 9:5, while the other materials, process parameters and processes are the same as in Example 1.

[0081] The prepared electrolyte membrane underwent tensile testing, exhibiting a tensile strength of 7.86 MPa and an elongation at break of 85.62%, which was achieved at room temperature at a rate of 0.2 mA cm⁻¹. -2 The constant current charge-discharge cycle can be stably maintained for about 450 hours at the specified current density.

[0082] Example 9

[0083] This embodiment is based on Example 1, except that the product ratio of plasticizer and interface modifier in preparation step (2) is 9:5, while the other materials, process parameters and processes are the same as in Example 1.

[0084] After fabricating the coin-type lithium battery, electrochemical tests were conducted. The initial discharge specific capacity at 0.1C rate was 160.2 mAh / g, and the coulombic efficiency was 97.89%.

[0085] Example 10

[0086] This embodiment is based on Example 1, except that the amount of nano-hydroxyapatite added in preparation step (2) is 0.05% of the total weight of the solute, and the other materials, process parameters and processes are the same as in Example 1.

[0087] The prepared electrolyte has an ionic conductivity of 1.52 × 10⁻⁶. -4 S / cm, after preparing coin-type lithium batteries, electrochemical tests were performed. The initial discharge specific capacity at 0.1C rate was 161.4 mAh / g, and the coulombic efficiency was 98.16%.

[0088] Example 11

[0089] This embodiment is based on Example 1, except that the amount of nano-hydroxyapatite added in preparation step (2) is 3% of the total weight of the solute, while the other materials, process parameters and processes are the same as in Example 1.

[0090] The prepared electrolyte has an ionic conductivity of 1.34 × 10⁻⁶. -4 S / cm, after preparing coin-type lithium batteries, electrochemical tests were performed. The initial discharge specific capacity at 0.1C rate was 157.9 mAh / g, and the coulombic efficiency was 98.24%.

[0091] Comparative Example 1

[0092] This comparative example is based on Example 1, except that nano-hydroxyapatite is not added in step (2), while the other materials, process parameters and processes are the same as in Example 1.

[0093] The prepared electrolyte membrane was subjected to tensile testing, and the tensile strength was 4.21 MPa, and the elongation at break was 45.67%.

[0094] After fabricating the coin-type lithium battery, electrochemical tests were conducted. The initial discharge specific capacity at 0.1C rate was 127.3 mAh / g, and the coulombic efficiency was 97.61%.

[0095] It is evident that introducing nano-hydroxyapatite as a filler during the preparation of electrolytes allows HAP to form hydrogen bonds with PVDF-HFP, enhancing its mechanical strength. It also promotes lithium-ion migration, constructs lithium-ion transport channels, and improves the discharge specific capacity.

[0096] Comparative Example 2

[0097] This comparative example is based on Example 1, except that no plasticizer is added in step (2), and only 90 μL of interface modifier (fluoroethylene carbonate) is added. All other materials, process parameters and processes are the same as in Example 1.

[0098] The prepared electrolyte has an ionic conductivity of 1.61 × 10⁻⁶. -4 S / cm, after preparing coin-type lithium batteries, electrochemical tests were conducted. The initial discharge specific capacity at 0.1C rate was 145.4 mAh / g, and the coulombic efficiency was 98.23%.

[0099] It is evident that the ionic conductivity and discharge specific capacity decrease significantly. This is because succinate, as a plasticizer, can reduce the crystallinity of PVDF-HFP, enhance the mobility of molecular chain segments, and promote the dissociation of lithium salts. Without plasticizers, the ionic conductivity would decrease.

[0100] Comparative Example 3

[0101] This comparative example is based on Example 1, except that the interface modifier (fluoroethylene carbonate) is not added in step (2), and only 210 μL of plasticizer (butadiene nitrile) is added. The other materials, process parameters and processes are the same as in Example 1.

[0102] Electrochemical tests were performed after fabricating coin-type lithium batteries at room temperature using 0.2 mA cm⁻¹. -2 The constant current charge-discharge cycle can be stably maintained for about 400 hours.

[0103] This comparative example verifies that introducing an interface modifier during the preparation of a solid electrolyte can help generate LiF to construct a stable SEI interface, thereby improving the cycle stability of lithium batteries.

[0104] Comparative Example 4

[0105] This comparative example is based on Example 1, except that the mass ratio of polyvinylidene fluoride-hexafluoropropylene and lithium salt in preparation step (2) is adjusted to 1:0.3. All other materials, process parameters and processes are the same as in Example 1.

[0106] After fabricating the coin-type lithium battery, electrochemical tests were conducted. The initial discharge specific capacity at 0.1C rate was 145.4 mAh / g, and the coulombic efficiency was 98.23%.

[0107] Comparative Example 5

[0108] This comparative example is based on Example 1, except that the mass ratio of polyvinylidene fluoride-hexafluoropropylene and lithium salt in preparation step (2) is adjusted to 9:4. All other materials, process parameters and processes are the same as in Example 1.

[0109] After fabricating the coin-type lithium battery, electrochemical tests were conducted. The initial discharge specific capacity at 0.1C rate was 146.7 mAh / g, and the coulombic efficiency was 98.67%.

[0110] As can be seen from Comparative Examples 4 and 5 above, the mass ratio of polyvinylidene fluoride-hexafluoropropylene to lithium salt is also very important. Its ratio regulates the crystallinity of the polymer and affects the degree of dissociation of lithium salt.

[0111] Comparative Example 6

[0112] This comparative example is based on Example 1, except that the product ratio of plasticizer and interface modifier in preparation step (2) is 2:1, while the other materials, process parameters and processes are the same as in Example 1.

[0113] The prepared electrolyte has an ionic conductivity of 1.24 × 10⁻⁶ at room temperature. -4 S / cm, after preparing coin-type lithium batteries, electrochemical tests were conducted. The initial discharge specific capacity at 0.1C rate was 145.3 mAh / g, and the coulombic efficiency was 97.59%.

[0114] Comparative Example 7

[0115] This comparative example is based on Example 1, except that the product ratio of plasticizer and interface modifier in preparation step (2) is 10:3, and the other materials, process parameters and processes are the same as in Example 1.

[0116] The prepared electrolyte had a tensile strength of 5.12 MPa and an elongation at break of 47.23%. Electrochemical tests were performed after fabricating a coin cell lithium battery at room temperature and at 0.2 mA cm⁻¹. -2 The constant current charge-discharge cycle can be stably maintained for about 470 hours at the specified current density.

[0117] As can be seen from Comparative Examples 6 and 7 above, the product ratio of plasticizer and interface modifier is also very important. Succinitriles affect the crystallinity of the polymer, thereby affecting its ionic conductivity. Fluorinated ethylene carbonate preferentially reduces on the lithium metal anode surface to construct a stable SEI film rich in LiF, suppressing interfacial side reactions and lithium dendrite growth. The ratio of the two will regulate the lithium-ion solvation sheath structure. An excessively high SN ratio will hinder FEC from participating in interfacial film formation and reduce the LiF content in the SEI; an excessive FEC will weaken the plasticizing effect of SN and simultaneously cause continuous irreversible consumption of metallic lithium. Only an appropriate ratio can balance the ion conductivity of the electrolyte bulk and the stability of the anode interface.

[0118] Comparative Example 8

[0119] This comparative example is based on Example 1, except that the content of nano hydroxyapatite in step (2) is 5%, while the other materials, process parameters and processes are the same as in Example 1.

[0120] The prepared electrolyte has an ionic conductivity of 0.97 × 10⁻⁶ at room temperature. -4 S / cm. Electrochemical tests were conducted after fabricating the coin-type lithium battery. The initial discharge specific capacity at 0.1C rate was 150.6 mAh / g, and the coulombic efficiency was 98.77%. It can be seen that the ionic conductivity is significantly reduced. This may be because the introduction of too much nano-hydroxyapatite as a filler will lead to blockage of ion transport channels. Excessive nano-hydroxyapatite will hinder the transport of lithium ions.

[0121] Comparative Example 9

[0122] This comparative example is based on Example 1, except that the plasticizer in preparation step (2) is adiponitrile, and the other materials, process parameters and processes are the same as in Example 1.

[0123] The prepared electrolyte underwent tensile testing, showing a tensile strength of 4.1 MPa, an elongation at break of 40.26%, and an ionic conductivity of 0.89 × 10⁻⁶. -4 S / cm.

[0124] It can be seen that the mechanical properties and ionic conductivity are significantly reduced. This is because the adiponitrile molecular chain is longer, the steric hindrance is increased, the ability to dissociate lithium salt is reduced, and the degree of crystallization of PVDF-HFP is reduced, resulting in poorer mechanical properties and conductivity of the prepared electrolyte membrane.

[0125] Comparative Example 10

[0126] This comparative example is based on Example 1, except that the interface modifier in preparation step (2) is ethylene carbonate, while the other materials, process parameters and processes are the same as in Example 1.

[0127] The prepared electrolyte has an ionic conductivity of 0.81 × 10⁻⁶ at room temperature. -4 S / cm, at room temperature at 0.2 mA cm -2 The constant current charge-discharge cycle can be stably cycled for about 310 hours at a current density. The ionic conductivity and long-term cycle stability are significantly reduced because ethylene carbonate preempts the Li+ solvation shell sites, weakens the effect of SN in promoting lithium salt dissociation, and makes it difficult to uniformly control lithium deposition, which reduces the ability to suppress lithium dendrites and increases interfacial side reactions, thus leading to poor cycle stability.

[0128] Comparative Example 11

[0129] This comparative example is based on Example 1, except that in step (2) the nano hydroxyapatite is changed to nano silica, and the other materials, process parameters and processes are the same as in Example 1.

[0130] The prepared electrolyte has an ionic conductivity of 1.57 × 10⁻⁶ at room temperature. -4 The tensile strength is 6.84 MPa, and the elongation at break is 86.74%.

[0131] It can be seen that both ionic conductivity and mechanical properties have decreased. This is because SiO2 has a lower hydroxyl density and weaker acidity, resulting in limited ability to inhibit PVDF-HFP crystallization and fewer ion conduction channels. Its effect on promoting the dissociation of TFSI⁻ associative polymers is also limited, making it difficult to sufficiently weaken ion aggregation. Furthermore, the interaction between SiO2 and the polymer is weak, with SiO2 primarily acting as a physical filler, thus limiting its reinforcing effect.

[0132] Comparative Example 12

[0133] This comparative example is based on Example 1, except that the lithium salt in preparation step (2) is changed to lithium hexafluorophosphate. All other materials, process parameters and processes are the same as in Example 1.

[0134] The prepared electrolyte has an ionic conductivity of 0.79 × 10⁻⁶ at room temperature. -4 S / cm, at room temperature at 0.2 mA cm -2 The constant current charge-discharge cycle can be stably cycled for about 360 hours at a given current density. However, the ionic conductivity and cycle stability both decrease significantly. This is because lithium hexafluorophosphate is highly susceptible to hydrolysis, and heating accelerates this hydrolysis, generating PF5 Lewis acids. This leads to polymer matrix degradation, voids in the electrolyte membrane, and impairs FEC film formation, thus resulting in decreased cycle stability.

[0135] Comparative Example 13

[0136] This comparative example is based on Example 1, except that the reagent in preparation step (2) is changed to methanol, while the other materials, process parameters and processes are the same as in Example 1.

[0137] After preparing the coin cell lithium battery, electrochemical tests were conducted. The initial discharge specific capacity at 0.1C rate was 144.6 mAh / g, and the coulombic efficiency was 97.45%.

[0138] The discharge specific capacity was significantly reduced after the reagent in this comparative example was changed to methanol. This is because methanol cannot effectively dissolve polyvinylidene fluoride-hexafluoropropylene, making it difficult to prepare a uniform precursor solution. At the same time, the active hydroxyl groups can easily trigger lithium salt hydrolysis, and the rapid volatilization during the film formation process can easily cause film defects. Residual alcohol impurities will aggravate the side reactions at the lithium anode interface and destroy the synergistic modification effect of each component.

[0139] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, are covered within the scope of protection of the present invention.

Claims

1. A method for preparing a multi-component synergistically modified solid-state lithium battery, characterized in that, It includes the following steps: S1. Preparation of composite solid electrolyte membrane: Polyvinylidene fluoride-hexafluoropropylene and lithium salt are mixed and then added to one of acetonitrile, nitrogen-methylpyrrolidone, ethanol, and methanol. The mixture is stirred at 30-70°C for 3-8 hours until the polymer is fully dissolved. Then, plasticizer and interface modifier are added and stirred at 40-70°C for 3-8 hours until fully dissolved. Finally, nano-hydroxyapatite (HAP) is added until the solution is uniformly mixed. The resulting slurry is coated, dried, and cut into sheets to prepare a multi-component synergistic modified composite solid electrolyte membrane. S2. Assemble the battery: Assemble the multi-component synergistic modified composite solid electrolyte membrane obtained in step S1 into a lithium metal battery system to obtain a multi-component synergistic modified solid lithium battery.

2. The method for preparing a multi-component synergistically modified solid-state lithium battery according to claim 1, characterized in that, The plasticizer is at least one selected from adiponitrile, malononitrile, succinic anhydride, glutaronitrile, azelaic anhydride, heptaic anhydride, caprylic anhydride, or sebacate.

3. The method for preparing polyvinylidene fluoride-hexafluoropropylene-based solid-state lithium batteries by multi-component synergistic modification according to claim 1, characterized in that, The lithium salt is any one of LiPF6, LiTFSI, LiFSI, LiBOB, LiDFOB, LiBF4, LiClO4, or LiAsF6.

4. The method for preparing a multi-component synergistically modified solid-state lithium battery according to claim 1, characterized in that, The interface modifier is at least one of fluoroethylene carbonate, ethylene carbonate, trifluoromethyl tert-butyl carbonate, tri(2,2,2-trifluoroethyl) borate, and vinyltriethoxysilane.

5. The method for preparing a multi-component synergistically modified solid-state lithium battery according to claim 1, characterized in that, The weight ratio of polyvinylidene fluoride-hexafluoropropylene, lithium salt and nitrogen-methylpyrrolidone is 2.5-20:1-15:15-50; the volume ratio of plasticizer and interface modifier is 5-10:1-6; and the amount of nano-hydroxyapatite added is 0.05-5.0% of the total weight of solute.

6. The method for preparing a multi-component synergistically modified solid-state lithium battery according to claim 1, characterized in that, The positive electrode sheet of the lithium-ion battery described in step S2 is prepared by the following method: polyvinylidene fluoride and plasticizer are added to nitrogen-methylpyrrolidone and stirred overnight to obtain a transparent solution. Lithium iron phosphate and acetylene black are ground and mixed evenly in a grinding mortar. The transparent liquid is then added to the grinding mortar and ground until the slurry becomes black and viscous. The ground slurry is coated onto aluminum foil and placed in a drying oven at 40-80°C for 10-48 hours. The foil is then cut into round sheets using a cutting machine.

7. A method for preparing a multi-component synergistically modified solid-state lithium battery according to claim 7, characterized in that, The plasticizer is at least one of malononitrile, succinic anionitrile, glutaronitrile, adiponitrile, heptacyanide, octanoic anionitrile, azelaic anionitrile, or sebacate; the weight ratio of lithium iron phosphate, polyvinylidene fluoride, acetylene black, and plasticizer is 6–10:0.1–2:0.1–2:0.1–2; the volume ratio of N-methylpyrrolidone to the mass ratio of lithium iron phosphate is 1–10 mL:1–3 g.

8. The method for preparing a multi-component synergistically modified solid-state lithium battery according to claim 1, characterized in that, The lithium-ion battery assembly in step S2 follows the sequence of positive electrode shell, positive electrode sheet, solid electrolyte membrane, negative electrode, stainless steel sheet, spring sheet, and negative electrode shell. The assembled battery is then placed on a battery sealing machine and pressurized to 450–650 kg·cm². -2 .